2021
DOI: 10.3390/reactions2010006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structure and Particle Size of Iron, Cobalt and Ruthenium Catalysts on Fischer–Tropsch Synthesis

Abstract: This review emphasizes the importance of the catalytic conversion techniques in the production of clean liquid and hydrogen fuels (XTF) and chemicals (XTC) from the carbonaceous materials including coal, natural gas, biomass, organic wastes, biogas and CO2. Dependence of the performance of Fischer–Tropsch Synthesis (FTS), a key reaction of the XTF/XTC process, on catalyst structure (crystal and size) is comparatively examined and reviewed. The contribution illustrates the very complicated crystal structure eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…They reported that the iron carbide is the most crucial active phase for olefin production through FT reaction, and also the larger pore size of iron-based catalysts could result in a higher olefin production and decrease the readsorption and secondary reactions. According to the findings reported in the literature, Yahyazadeh et al [115] and Ma and Dalai [116] also reported that the support's properties could significantly affect the catalyst performance. The desirable interaction with metal and support needs to be considered during the selection of the support.…”
Section: Zeolite Supported Catalystsmentioning
confidence: 94%
“…They reported that the iron carbide is the most crucial active phase for olefin production through FT reaction, and also the larger pore size of iron-based catalysts could result in a higher olefin production and decrease the readsorption and secondary reactions. According to the findings reported in the literature, Yahyazadeh et al [115] and Ma and Dalai [116] also reported that the support's properties could significantly affect the catalyst performance. The desirable interaction with metal and support needs to be considered during the selection of the support.…”
Section: Zeolite Supported Catalystsmentioning
confidence: 94%
“…This is manifested by the different FTS performances of the two catalysts, as shown in the previous sections. According to the literature, iron particle size is one of the parameters that has a profound effect in nanocatalysis, especially on FTS performance, including X CO , , , hydrocarbon selectivity, and FTY. , As noticed from the TEM data of this work, the average iron particle size of Fe-MIL-88B-T/C (5.8 nm) is far smaller than that of Fe-MIL-88B-S/C (35.0 nm). In general, Fe-MIL-88B-T/C shows higher X CO percentages than Fe-MIL-88B-S/C.…”
Section: Resultsmentioning
confidence: 63%
“…Several studies proposed that the textural properties of the support and the pore size and particle size of the active metal considerably impact catalytic activity and olefin selectivity. , However, the pore size effect appears to be overlapping with the particle size effect. , The effect of metal particle size on FTS performance has been generally studied on Fe, Co, and Ru catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…Two review contributions are included in this special issue as well. One review by Professors Ma and Dalai highlighted the effects of structure and particle size of Fe, Co, and Ru catalysts on Fischer-Tropsch Synthesis (FTS) [14,15]. The complicated crystal structure effect including phase type, for example, various iron carbides (Fe 7 C 3 , χ-Fe 5 C 2 , θ-Fe 3 C, ε-Fe 2 C), fcc and hcp cobalt and fcc and hcp ruthenium, phase shape, and crystal facets, were discussed and reviewed [14].…”
mentioning
confidence: 99%
“…One review by Professors Ma and Dalai highlighted the effects of structure and particle size of Fe, Co, and Ru catalysts on Fischer-Tropsch Synthesis (FTS) [14,15]. The complicated crystal structure effect including phase type, for example, various iron carbides (Fe 7 C 3 , χ-Fe 5 C 2 , θ-Fe 3 C, ε-Fe 2 C), fcc and hcp cobalt and fcc and hcp ruthenium, phase shape, and crystal facets, were discussed and reviewed [14]. Two particle size regions spitted at 7-8 nm were pointed out for all metals, and the useful intrinsic activity values of all metals were estimated, i.e., TOF 0.046-0.20 s −1 for Fe catalysts (10 nm) at 260-300 • C, 0.1 s −1 and 0.4 s −1 (the highest) for Co and Ru catalysts (7-70 nm) at 220 • C, respectively.…”
mentioning
confidence: 99%